Energy multi-scale method to analyze the scale effect of soil particles - Chen, Jian; Tong, Huawei; Yuan, Jie; Fang, Yingguang; Huang, Xiaofeng (Frontiers in Materials, 2023)
The characteristics of particles affect the properties of soil in macroscope, so soil shows an obvious scale effect. In order to explain the internal mechanism of the soil scale effect, this paper starts with the microscopic force of particles, explores the influence of particle composition and geometric scale on the particle surface and interface state, then proposes an energy multiscale method. Finally, the mechanism of clay plasticity index change was quantitative explained by energy multiscale method. Through these works, three conclusions were draw: (1) Both the mineral composition and particle size of the soil can cause interface effects and surface effects. (2) The comprehensive ratio of micro-force to weight (CRFW) of the particles by energy multiscale method can quantitatively reflect the influence of the particle size and mineral composition on the properties of the soil in microscope. (3) The energy multiscale method can explain the mechanism of plasticity index of plastic soil and realize the new division of plastic soil. When the CRFW was used as the control index, even if the mineral composition and the particle size of three materials were different, but the plasticity index of the three materials was basically the same.